As moedas digitais na disputa pela ordem monetária internacional entre China e Estados Unidos - Rodrigues, Iuri Pruni (My University, 2025)
In the context of international business, digital currencies are emerging as an innovation with the potential to drive significant changes in the international monetary system. This trend is evidenced by the advancement of central bank digital currency (CBDC) projects, particularly the e-CNY, an initiative led by China, which, together with the development of stablecoins, especially those backed by the U.S. dollar, signals possible transformations in global payment systems. In this context, marked by the hegemony of the U.S. dollar as the main currency in international trade, it becomes pertinent to analyze the implications of this evolving scenario. This study aimed to discuss the role of digital currencies in the economic and monetary competition between China and the United States. To this end, a qualitative exploratory study was conducted, based on a literature review and observation at an event featuring specialists in digital currencies and the financial market. The results revealed that, although the topic calls for further studies and regulatory developments due to its contemporary nature, digital currencies are advancing toward practical applications in international trade, with Brazilian companies already conducting transactions in this format. In the global landscape, China and the United States follow distinct strategies consistent with their political-economic profiles: China, with a more centralized system, is investing heavily in the development of its CBDC, while the United States, with a more liberal profile, encourages the use of dollar-backed stablecoins. [resumo fornecido pelo autor]
No contexto dos negócios internacionais, as moedas digitais emergem como uma inovação com potencial para promover mudanças significativas no sistema monetário internacional. Essa tendência é evidenciada pelo avanço dos projetos de moedas digitais emitidas por bancos centrais (CBDCs), com destaque para o e-CNY, iniciativa liderada pela China, que, juntamente com o desenvolvimento das Stablecoins, principalmente lideradas por aquelas lastreadas no dólar dos Estados Unidos, sinalizam possíveis transformações nos sistemas de pagamentos globais. Nesse contexto, marcado pela hegemonia do dólar americano como principal moeda no comércio internacional, torna-se pertinente analisar as implicações desse cenário em transformação. Este estudo teve como objetivo discutir o papel das moedas digitais na disputa econômico-monetária entre China e Estados Unidos. Para tanto, foi desenvolvida uma pesquisa qualitativa de nível exploratório, com base em pesquisa bibliográfica e observação em evento com especialistas na área de moedas digitais e do mercado financeiro. Os resultados revelaram que, embora o tema enseje novos estudos e regulamentações, até por sua contemporaneidade, as moedas digitais estão avançando para aplicações práticas no comércio internacional, com empresas brasileiras já realizando transações nesse formato. No cenário global, China e Estados Unidos seguem estratégias distintas, coerentes com seus perfis político-econômicos, a China, mais centralizada, investe fortemente no desenvolvimento de sua CBDC, enquanto os Estados Unidos, de perfil mais liberal, estimulam o uso de stablecoins lastreadas em dólar. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Criptomoedas; Transferência eletrônica de fundos; Moeda digital de banco central; Moeda - China - Estados Unidos